2016
DOI: 10.3103/s1068366616020124
|View full text |Cite
|
Sign up to set email alerts
|

Method of evaluating the coefficient of friction of frost-resistant sealing rubbers

Abstract: The results of an experimental study of the effect of the normal pressure in the range of 0.1-0.3 MPa, a velocity of sliding of 1-100 mm/s, and a bulk temperature of 22 to -27°C on the coefficient of sliding friction of an elastomer-steel friction pair have been presented. Two types of elastomeric materials have been considered, i.e., frost resistant rubber based on synthetic propylene oxide rubber and this rubber filled with the antifriction additive of ultrafine polytetrafluoroethylene powder in an amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…Meanwhile, due to cyclic deformations of the rubber by asperities of sandpaper in the process of sliding friction a second weak maximum of the coefficient of friction, is observed [3,4]. In fact, one of the authors of this work has shown [5] that, a second weak maximum at friction of rubber against smooth well-polished steel in the same testing conditions, was not observed. From the results (figure 2) it is evident that normal pressure has a strong influence on the coefficient of friction.…”
Section: Results and Discusionmentioning
confidence: 81%
“…Meanwhile, due to cyclic deformations of the rubber by asperities of sandpaper in the process of sliding friction a second weak maximum of the coefficient of friction, is observed [3,4]. In fact, one of the authors of this work has shown [5] that, a second weak maximum at friction of rubber against smooth well-polished steel in the same testing conditions, was not observed. From the results (figure 2) it is evident that normal pressure has a strong influence on the coefficient of friction.…”
Section: Results and Discusionmentioning
confidence: 81%
“…А.Ю. Ишлинского РАН (г. Москва) на трибометре UMT-2 по методике, изложенной в работах [39,44], сопротивление резин абразивному износу также изучали на машине трения МИ-2 и приборе АР-40.…”
Section: материалы и методы исследованияunclassified
“…А.Ю. Ишлинского РАН (г. Москва) [39,44] для резины, содержащей 50 мас.ч. УПТФЭ, были детально исследованы триботехнические свойства разработанного материала при комнатной и отрицательной температурах.…”
Section: T a B L E 1 The Main Properties Of Rubbers Based On Mixturesunclassified
“…UPTFE (brand name: “Forum”) is a PTFE with a molecular weight that is relatively lower than that of ordinary PTFE [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. UPTFE has unique thermal and aggressive media resistance, chemical resistance, a low coefficient of friction, and can withstand temperatures of −169 °C to 270 °C [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%